Classifying OECD healthcare systems: A deductive approach - Katharina Böhm; Achim Schmid; Ralf Götze; Claudia Landwehr; Heinz Rothgang (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2012)
This paper is a first attempt to classify 30 OECD healthcare systems according to a typology developed by Rothgang et al. (2005) and elaborated by Wendt et al. (2009). The typology follows a deductive approach. It distinguishes three core dimensions of the healthcare system: regulation, financing, and service provision. Moreover, three types of actors are identified based on long-standing concepts in social research: the state, societal actors, and market participants. Uniform or ideal-type combinations unfold if all dimensions are dominated by the same actor, either belonging to the state, society, or the market. Further, we argue, there is a hierarchical relationship between the dimensions of the healthcare system, led by regulation, followed by financing, and last service provision, where the superior dimension restricts the nature of the subordinate dimensions. This hierarchy limits the number of theoretically plausible healthcare system types within the logic of the deductive typology. The classification of 30 countries according to their most recent institutional setting results in five healthcare system types: the National Health Service, the National Health Insurance, the Social Health Insurance, the Etatist Social Health Insurance, and the Private Health System. Of particular relevance are the National Health Insurance and the Etatist Social Health Insurance both of which include countries that have often provoked caveats when allocated to a specific family of healthcare systems. Moreover, Slovenia stands out as a special case. The findings are discussed with respect to alternative taxonomies, explanatory factors for the position of single countries and most likely trends. – – Dieses Paper ist ein erster Versuch 30 OECD-Gesundheitssysteme anhand einer Typologie zu klassifizieren, die von Rothgang et al. (2005) vorgestellt und von Wendt et al. (2009) weiterentwickelt wurde. Im Gegensatz zu bestehenden Taxonomien folgt diese Typologie einem deduktiven Ansatz. Sie unterscheidet zwischen den drei Kerndimensionen eines Gesundheitssystems: Regulierung, Finanzierung und Leistungserbringung. Darüber hinaus werden auf Grundlage bestehender sozialwissenschaftlicher Konzepte drei Akteure unterschieden: Staat, gesellschaftliche Akteure und Marktteilnehmer. Idealtypische Konstellationen treten auf, wenn alle Dimensionen vom gleichen Akteur (Staat, Gesellschaft oder Markt) dominiert werden. Wir argumentieren zudem, dass es eine hierarchische Beziehung zwischen den drei Dimensionen gibt. Dabei nimmt die Regulierung die übergeordnete Stellung ein, gefolgt von der Finanzierung und schließlich der Leistungserbringung, wobei die Ausprägung vorrangiger Dimensionen die Ausgestaltungsoptionen der nachrangingen limitiert. Diese Hierarchie reduziert die Zahl der theoretisch plausiblen Gesundheitssystemtypen im Rahmen des deduktiven Ansatzes. Die Klassifizierung von 30 OECD-Ländern anhand ihrer gegenwärtigen institutionellen Ausprägungen führt zu fünf Gesundheitssystemtypen: Nationaler Gesundheitsdienst, nationales Krankenversicherungssystem, Sozialversicherungssystem, etatistisches Sozialversicherungssystem und privates Gesundheitssystem. Von besonderer Bedeutung sind die Typen nationales Krankenversicherungssystem und etatistisches Sozialversicherungssystem da beide in Staaten auftreten, deren Zuordnung zu bestimmten Gesundheitssystemtypen bisher umstritten war. Darüber hinaus sticht Slowenien als Ausnahmefall aus dem Ländersample hervor. Die Ergebnisse werden im Hinblick auf alternative Typologien, mögliche Erklärungsfaktoren für die Einordung einzelner Länder und wahrscheinliche Entwicklungstrends diskutiert.
Keywords: 300